Zooplankton community structure in relation to the water quality and seston fatty acid content in the coastal waters of Penang, Malaysia - Wan Maznah W.O.; Nur ‘Ain Kassim; Zubir Din (Penerbit Universiti Kebangsaan Malaysia, 2021)
Zooplankton community structure and seston fatty acid content in relation with water quality characteristics at selected sampling stations of Penang coastal waters were determined. Water and zooplankton samples were collected on five sampling occasions from July 2009 until April 2011. Zooplankton samples were collected by horizontal towing with plankton net (WP-2) and a fraction of the samples was used to get seston population for fatty acid analysis. Phylum Arthropoda dominated the sampling area with 78.80% of relative abundance, where Copepoda was the most abundant. Other phyla such as Chordata (9.10%), Cycliophora (6.12%), Actinopoda (2.08%), Rotifera (2.57%), Annelida (0.63%), Cnidaria (0.51%), and Chaetognatha (0.19%) were accounted in small abundance. Kuala Juru Station, which was highly impacted by human activities had the highest relative abundance and Jerejak Station (control station and considered to have low impact by anthropogenic activities) had the lowest relative abundance. Zooplankton diversity was quite low at all stations, might be due to large abundance of dominant taxa. The dominant fatty acid methyl esters (FAMEs) detected on seston consisted of SAFA (C16:0, C14:0, and C18:0), MUFA (C16:0, C14:0, and C18:0), PUFA (C18:2n6c and C20:5n3) and HUFA (C22:6n3 or DHA). Zooplankton community was influenced by food availability (phytoplankton, as measured by chlorophyll a and fatty acid composition in seston) and water quality.